Investigating how teacher support promotes student engagement in Somali EFL classrooms: the role of academic resilience and student demographics - Mohamud, Mohamed Ahmed; Khalaf, Mohamed A. A.; Abdulle, Abdirizak Warsame; Barre, Ahmed Osman (Frontiers in Education, 2026)
IntroductionEngaging learners in English as a Foreign Language (EFL) class is a major challenge in resource-limited environments like Somalia. This study, being the first conducted in Somalia, is set out to examine the impact of teacher support (TS) on student engagement (SE) and academic resilience (AR), the mediation role of AR between TS and SE, and the moderation effect of gender and study year.MethodsData were collected from 559 EFL learners attending the Faculty of Computer & IT at Jamhuriya University of Science and Technology using a self-reported, cross-sectional online survey. TS, AR, and SE were measured using Students’ Perceived EFL Teacher Support Scale (SPEFLTSS), Student Engagement in Schools Questionnaire (SESQ), and Language Learner’s Resilience Scale (LLRS), respectively. Data was analyzed using SmartPLS 4.1.0.6, utilizing partial least squares structural equation modelling (PLS-SEM).ResultsThe findings suggested that TS had a strong positive impact on SE and AR, while AR also acted as a strong predictor of SE. Mediation analysis showed that AR partially mediated the relationship between TS and SE, while moderation analysis revealed that the impact of TS on SE was stronger in the 2023 cohort in comparison with the 2024 cohort, and that TS had a bigger effect on AR in male students than in their female counterparts. The suggested model explained almost half (47.3%) of the overall variance in student engagement, indicating a robust predictive power.DiscussionThese findings underline the two-fold role of TS in sustaining SE and nurturing AR, while also emphasizing that this influence is formed by learners’ demographics and background. These results have implications for EFL teachers and policymakers to develop professional development programs, integrate resilience-building activities into the curriculum and foster conducive and responsive EFL environments in the Somali higher education landscape.